INFLUENCE OF THE LEVEL OF EDUCATION ON PROGRESSION OF WOMEN TO LEADERSHIP POSITIONS - A., M.A, OSIJE, Majina; M. O., PhD, Dr. YAMBO John (IJRDO - Journal of Applied Management Science, 2016)
The study was conducted in Mabera division, Kuria west, Migori County to investigate the factors that influence to progression of women to leadership positions. The 1995 Beijing Platform for Action, emphasized that ‘women’s equal participation in decision making is not only a demand for justice or democracy, but can also be seen as a necessary condition for women’s interests to be taken into account. The objective of the article was to determine the influence of the level of education on progression of women to leadership position in Mabera Division, Migori County. The study was guided by The Classical Liberal Theory of Equity of Opportunity (Classical liberalism or libertarianism) that holds that women and men are self-owners capable of acquiring property rights over things. The study used descriptive survey that targeted a population of 9523 women from different households within the division. The Krejcie, Robert V., Morgan table was used to calculate the sample population size and that gave the researcher a sample size of 373 women interviewed. Questionnaires were used as research instruments which the respondents filled during the survey. Data collected from the field was coded and ultimately analyzed by performing several descriptive statistical computations such as frequency distribution tables and measures of central tendencies. Frequency tables were used to present data. The study revealed that majority of women interviewed 48.4% had primary level of education and only 35.8% managed to reach secondary level. Generally, this implies low levels of education in the area as far as women education is concerned. The researcher concluded that there is need to educate girl child in the division so that they can participate in leadership. The researcher recommended that Leadership Forums & Social Networking gatherings should provide opportunities for women to exchange experience and wisdom with other women in equivalent positions